Magic, Riley County - Porter, Anthony (Kansas State University, The Chapman Center for Rural Studies, 2015)
The lost community of Magic, located in Riley County, Kansas, was settled by immigrants from Germany in a process of chain migration. The community’s population steadily began to decline in the 1930s and was eventually consumed by the expansion of Fort Riley Military Reservation during the Cold War. This study provides a history of Magic using newspapers, maps, photographs, various book segments, and an interview of a longtime resident of the area.
Anthony Porter, “Magic, Riley County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/157.
Keywords: Fort Riley; Magic; Riley County; Fort Riley Military Reservation; Magic Stock Farm; West German Conference